PENGGUNAAN MEDIA PEMBELAJARAN SIMULASI PHET (PHYSICS EDUCATION TECHNOLOGY) UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATERI INDUKSI ELEKTROMAGNETIK KELAS XII SMA NEGERI 1 KAMPAR TIMUR - Sutri, Nilma; Azizahwati, Azizahwati; Nor, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to describe and determine the increase in student learning motivation by using PhET simulation learning media on electromagnetic induction material for class XII SMA Negeri 1 Kampar Timur. This type of research is quantitative, and the research design used was the pretest-posttest control group design. The subjects of this study were students of class XII SMA Negeri 1 Kampar Timur who were divided into two classes, namely the experimental class and the control class. The data in this study were in the form of learning motivation scores before and after learning physics using the PhET simulation learning media which were analyzed descriptively. Furthermore, the increase in motivation was analyzed by the Independent Sample T Test and Paired Sample T Test. Based on the data analysis, it was found that the final motivation of students in the experimental class was in the high category with an average increase in motivation of 1.14, while the control class was in the low category of 0.34. Thus it can be concluded that the application of using PhET simulation learning media can increase student motivation in SMA Negeri 1 Kampar Timur.Key Words: PhET Simulation Learning Media, Learning Motivation